Monocyte-to-Lymphocyte Ratio (MLR) as a Possible Prognostic Marker of Latent Tuberculosis (LTBI) among Household Contacts of Active Tuberculosis (TB) Patients - Khurshid, Rukhshan; Sijjeel, Farwa; Asim, Samar; Mahmood, Maira; Ashraf, Huma; Rashid, Shazia; Khan, Muhammad Yousaf; Abbas, Safdar; Nawaz, Basharat; Naeem, Mashal; Malik, Noor Ul Ain (BioScientific Review, 2022)
Tuberculosis (TB) is endemic in many low socio-economic/developing countries including Pakistan. It is a leading cause of death from a single infectious agent worldwide. Identification and early treatment of latent conditions help reduce the complications associated with TB. However, the identification of individuals with latent infection is a time taking and expensive process. According to previous studies, a promising and cheap biomarker of TB may be the monocyte-to-lymphocyte ratio (MLR). It may indicate a body’s immune response to Mycobacterium tuberculosis. Since household contacts of tuberculosis (TB) patients have an increased risk of latent tuberculosis (LTBI), using the established diagnostic procedures as well as checking their MLR might help determine if they contracted LTBI or not. We conducted a cross-sectional study to determine if MLR could be used to identify LTBI among household contacts of patients with active tuberculosis. Out of the 100 subjects selected for this study, about 40 patients were recently diagnosed with active tuberculosis, 40 were close contacts of these patients, while 20 were chosen to be controls. The mean MLRwas 0.165, 0.06 (range 0.03–0.08), and 0.04 (0.02–0.04) in patients with active tuberculosis, close contacts of patients, and control subjects, respectively. Hence, it was determined that MLR (> 06 %) is a significant predictor for LTBI and can be used to diagnose it in close contacts of TB patients. It was additionally observed that patients over the age of 50 with pulmonary tuberculosis have higher MLR. Ratio of monocytes to lymphocytes (> 0.06) may help in diagnosing latent tuberculosis in close contacts of tuberculosis patients.